Emulsion-Based Postbiotic Formulation Is Comparable to Viable Cells in Eliciting a Localized Immune Response in Dairy Cows With Chronic Mastitis - Mathur, Harsh; Linehan, Kevin; Flynn, James; Byrne, Noel; Dillon, Pat; Conneely, Muireann; Grimaud, Ghjuvan; Hill, Colin; Stanton, Catherine; Ross, R. Paul (Frontiers in Microbiology, 2022)
Bovine mastitis is a disease with a multi-etiological nature, defined as an infection and inflammation of the udder. Mastitis represents a significant ongoing concern in the dairy industry, leading to substantial losses in profits and revenue for farmers worldwide. The predominant causes of bovine mastitis include the pathogens Staphylococcus aureus, Streptococcus dysgalactiae, Streptococcus uberis, and Escherichia coli. Antibiotic administration is currently the main treatment option for mastitis. However, there is a pressing need for alternative therapies to treat and prevent the disease, especially with the emergence of antibiotic-resistant, mastitis-causing pathogens, resulting in antibiotic treatment failure. One such example is live bio-therapeutics (also known as probiotics), such as Lactococcus lactis DPC3147. The efficacy of this live bio-therapeutic has been demonstrated in several previous trials by our group. The most recent of these trials showed that an emulsion-based formulation of this strain was as effective as a commercial antibiotic formulation in treating sub-clinical and clinical cases of bovine mastitis (Kitching et al., 2019). Here, we report the results of a follow-up field trial, in which we sought to gain insights into the mechanism of action of such live bio-therapeutics, focussing on chronic mastitis cases. We treated 28 cows with chronic mastitis with two separate emulsion-based formulations containing either viable L. lactis DPC3147 cells (15 cows) or heat-killed L. lactis DPC3147 cells (13 cows). We then evaluated the efficacies of the two formulations (two treatment groups) in terms of stimulating a localized immune response (quantified by measuring IL-8 concentrations in milk collected from udders affected by mastitis) and efficacies in terms of cure rates (quantified by reductions in somatic cell counts and absence of pathogens). We demonstrate that the presence of heat-inactivated bacteria (a postbiotic) was as effective as the live bio-therapeutic in eliciting a localized immune response in cows with chronic mastitis. The response to heat-killed cells ( postbiotic) reported herein could have beneficial implications for farmers with regards to prolonging the shelf-life of such emulsion-based formulations containing heat-killed cells of L. lactis DPC3147 for curing cows with mastitis.